2008
DOI: 10.1136/jnnp.2007.118786
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive declines following bilateral subthalamic nucleus deep brain stimulation for the treatment of Parkinson's disease

Abstract: Our findings demonstrated that patients who underwent DBS experienced declines in verbal recall and trends for declines in oral information processing 6 months following surgery, even when good motor outcome was achieved. Potential candidates should be counselled about the risk of mild frontostriatal cognitive declines following DBS to weigh the risks and benefits of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
123
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 38 publications
15
123
3
2
Order By: Relevance
“…Contrasting neuropsychological data have been reported on PD patients treated with STN-DBS: some studies suggested that cognitive outcomes might follow the natural history of the disease [5,28] , whereas others reported an increased risk of dementia early after surgery [29,30] .…”
Section: Follow-up Therapymentioning
confidence: 86%
“…Contrasting neuropsychological data have been reported on PD patients treated with STN-DBS: some studies suggested that cognitive outcomes might follow the natural history of the disease [5,28] , whereas others reported an increased risk of dementia early after surgery [29,30] .…”
Section: Follow-up Therapymentioning
confidence: 86%
“…10,28,29,33,35,65 However, a large multicenter study 91 found that the completed suicide rate following subthalamic DBS in PD is less than 0.5%, suggesting that suicide occurrences are unlikely to influence data significantly in this regard. We found that there are no long-term studies comparing the several therapeutic strategies for PD that adequately report objective data concerning anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, normal pre-operative cognitive functioning is positively correlated with postoperative improvement in UPDRS part III at a long-term follow-up [18]. STN-DBS may still lead to a decline in cognitive and executive function even with strict inclusion criteria [24]; however, it has been suggested that sub-optimal contact stimulation (caused by the small volume of STN) is more strongly correlated with post-operative psychiatric events. Although there are still debates about post-operative psychiatric events, the possibility of increased depression and suicide risk prompts us to evaluate the patient's psychological function in detail prior to the operation.…”
Section: Cognitive Psychiatric and Other Non-motor Symptomsmentioning
confidence: 95%